2012
DOI: 10.1146/annurev-publhealth-031811-124658
|View full text |Cite
|
Sign up to set email alerts
|

Health Inequalities: Trends, Progress, and Policy

Abstract: Health inequalities, which have been well documented for decades, have more recently become policy targets in developed countries. This review describes time trends in health inequalities (by sex, race/ethnicity, and socioeconomic status), commitments to reduce health inequalities, and progress made to eliminate health inequalities in the United States, United Kingdom, and other OECD countries. Time-trend data in the United States indicate a narrowing of the gap between the best- and worst-off groups in some h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
187
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(200 citation statements)
references
References 47 publications
8
187
0
5
Order By: Relevance
“…For example, Campos-Matos et al point to a ‘real or perceived lack of evidence on health inequalities’ in Portugal as a barrier to taking policy action to address health inequalities [14]. The UK has regular and systematic reporting of national health inequality monitoring, whereas the USA does not [15]. Low- and middle-income countries often do not have sufficient integration of health inequality monitoring into their health information systems; some middle-income countries, however, have institutionalized regular health inequality monitoring in some health topics.…”
Section: Key Challengesmentioning
confidence: 99%
“…For example, Campos-Matos et al point to a ‘real or perceived lack of evidence on health inequalities’ in Portugal as a barrier to taking policy action to address health inequalities [14]. The UK has regular and systematic reporting of national health inequality monitoring, whereas the USA does not [15]. Low- and middle-income countries often do not have sufficient integration of health inequality monitoring into their health information systems; some middle-income countries, however, have institutionalized regular health inequality monitoring in some health topics.…”
Section: Key Challengesmentioning
confidence: 99%
“…Modeling age-adjusted rates has been used in other studies examining trends in population-level health inequalities. 20 We estimated initiation rates for each income quintile; income-specific rates were estimated at provincial and hospital levels. Age-adjusted rates were estimated at the provincial level.…”
Section: Breastfeeding Initiation Ratesmentioning
confidence: 99%
“…Other covariates are known to predict breastfeeding at the individual-level; 4, 5 stratifying on these characteristics may yield differing trends in breastfeeding inequalities over the study period. 20,23 Observed trends in inequalities are not generalizable. Other studies using different populations will likely find differing trends.…”
Section: Limitations and Strengthsmentioning
confidence: 99%
“…36,106,176 Previous studies have found reductions in absolute socioeconomic inequality in overall mortality in England in the 2000s 177 and reductions in both absolute and relative inequality in life expectancy. 178 This is all in line with our findings.…”
Section: Overall Mortalitymentioning
confidence: 99%
“…[103][104][105] In England, data from 2001 to 2013 showed that preventable hospitalisations make up one in every five hospital admissions, and have increased by 48% in the last 12 years. 106 Common causes of preventable hospitalisations include urinary tract infection/ pyelonephritis, pneumonia, chronic obstructive pulmonary disease (COPD), convulsions and epilepsy, and ear, nose and throat infections. Studies suggest that preventable hospitalisation can be reduced by improving primary care supply and quality.…”
Section: Preventable Hospitalisationmentioning
confidence: 99%